The application of artificial intelligence to journalism: an analysis of academic production - Parratt-Fernández, Sonia; Mayoral-Sánchez, Javier; Mera-Fernández, Montse (El profesional de la informacion, 2021)
Journalism has been able to adapt quickly to technological innovation, especially in recent years. The application of algorithms and artificial intelligence (AI) to this discipline is a phenomenon that has developed rapidly in a very short time. This is therefore a research area that, in spite of its short life, deserves special interest. The objective of this review article is to map and analyze the global scientific production on this topic and to identify which countries are most focused on this issue, which areas are studied most and using which methodological approaches, how and where it is evolving, and the gaps present in this research. The review of 358 texts confirms the considerable attention from academia during the last decade, especially between 2015 and 2020, and that the USA is, by far, the country with most publications on this subject. Most of the published works are research articles carried out, above all, using qualitative methodologies. The areas that have attracted the most interest to date are data journalism, robot writing, and news verification. As is to be expected in a developing discipline, others such as the review of the role of the journalist, the personalization of content, or the incorporation of AI into teaching of journalism have not yet been sufficiently explored but surely will be in the near future.